The temporal primacy of self-related stimuli and negative stimuli: an ERP-based comparative study. (2nd September 2016) - Zhu, Min; Luo, Junlong; Zhao, Na; Hu, Yinying; Yan, Lingyue; Gao, Xiangping
ABSTRACT: Numerous studies have shown there exist attention biases for self-related and negative stimuli. Few studies, however, have been carried out to compare the effects of such stimuli on the neural mechanisms of early attentional alertness and subsequent cognitive processing. The purpose of the present study was to examine the temporal primacy of both self-related stimuli and negative stimuli in the neurophysiologic level. In a modified oddball task, event-related potentials of the deviant stimuli (i.e., self-face, negative face and neutral face) were recorded. Results revealed that larger P2 amplitudes were elicited by self-related and negative stimuli than by neutral stimuli. Negative stimuli, however, elicited shorter P2 latencies than self-related and neutral stimuli. As for the N2 component, self-related and negative stimuli elicited smaller amplitudes and shorter latencies than neutral stimuli, but otherwise did not differ. Self-related stimuli also elicited larger P3 and late positive component (LPC) amplitudes than negative and neutral stimuli. The pattern of results suggests that the primacy of negative stimuli occurred at an early attention stage of processing, while the primacy of self-related stimuli occurred at the subsequent cognitive evaluation and memory stage.